2017
DOI: 10.1038/nn.4651
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and oscillatory substrates of fear extinction learning

Abstract: The mammalian brain contains dedicated circuits for both the learned expression and suppression of fear. These circuits require precise coordination to facilitate the appropriate expression of fear behavior, but the mechanisms underlying this coordination remain unclear. Using a novel combination of chemogenetics, activity-based neuronal-ensemble labeling, and in vivo electrophysiology, we found that fear extinction learning confers parvalbumin-expressing (PV) interneurons in the basolateral amygdala (BLA) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(200 citation statements)
references
References 50 publications
11
189
0
Order By: Relevance
“…It has been reported that the amygdala is a vital brain area correlated with the social and fear-related behaviors (Bickart et al, 2011). In particular, it was found that BLA actively participated in fear extinction processing, and the aberrant neuronal activation in the BLA was implicated in enhanced fear extinction (Bocchio et al, 2017;Davis et al, 2017). Thus, we hypothesized that neuronal activation in the BLA may be decreased by co-housing with a receptive mating partner.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that the amygdala is a vital brain area correlated with the social and fear-related behaviors (Bickart et al, 2011). In particular, it was found that BLA actively participated in fear extinction processing, and the aberrant neuronal activation in the BLA was implicated in enhanced fear extinction (Bocchio et al, 2017;Davis et al, 2017). Thus, we hypothesized that neuronal activation in the BLA may be decreased by co-housing with a receptive mating partner.…”
Section: Resultsmentioning
confidence: 96%
“…Communication between the PFC and BLA occurs, in part, through oscillations, which can be manipulated and evoked using train frequency stimulations to understand the contribution of different oscillatory patterns between the PFC and BLA. Some of these oscillations from the PFC to the BLA are believed to be regulated by and sufficient to recruit inhibitory networks regulating fear expression [40,41]. While the current cortical train stimulation frequency (20 Hz) was chosen based on developmental differences between adults and adolescents seen throughout the BLA, future work should investigate the contribution of various frequency train ranges [18].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this prior work, we found that LB led to an earlier rise in PV+ cell density in BLA, with PV+ cell density being higher in LB reared mice compared to controls at PND 21. PV+ neuronal activity in the BLA has been shown to be capable of modulating fear expression (Wolff et al, 2014;Davis et al, 2017) . In addition, PV+ cell density has previously been shown to negatively correlate with innate threat responses in post-weaned rats (Santiago et al, 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…To understand the neural basis of the suppressed fear expression at PND 21, we focused on the potential role of the premature differentiation of PV+ neurons in the BLA ( Figure 2A ). The focus on PV+ cells is related to previous reports that have demonstrated a role for BLA PV+ cells in modulating fear expression (Wolff et al, 2014;Davis et al, 2017) . Therefore, we hypothesized that the early emergence of PV+ cells in the pre-adolescent BLA may be leading to the decreased fear expression observed at PND 22.…”
Section: Pv Inhibition In Bla Rescues Fear Expression Deficitsmentioning
confidence: 99%